Next generation sequencing of pancreatic cyst fluid microRNAs from low grade-benign and high grade-invasive lesions. Issue 2 (28th January 2015) - Wang, Jin; Paris, Pamela L.; Chen, Jinyun; Ngo, Vy; Yao, Hui; Frazier, Marsha L.; Killary, Ann M.; Liu, Chang-Gong; Liang, Han; Mathy, Christian; Bondada, Sandhya; Kirkwood, Kimberly; et al.
Abstract: Intraductal papillary mucinous neoplasm (IPMN) is a precursor cystic lesion to pancreatic cancer. With the goal of classifying IPMN cases by risk of progression to pancreatic cancer, we undertook an exploratory next generation sequencing (NGS) based profiling study of miRNAs (miRNome) in the cyst fluids from low grade-benign and high grade-invasive pancreatic cystic lesions. Thirteen miRNAs (miR-138, miR-195, miR-204, miR-216a, miR-217, miR-218, miR-802, miR-155, miR-214, miR-26a, miR-30b, miR-31, and miR-125) were enriched and two miRNAs (miR-451a and miR-4284) were depleted in the cyst fluids derived from invasive carcinomas. Quantitative real-time polymerase chain reaction analysis confirmed that the relative abundance of tumor suppressor miR-216a and miR-217 varied significantly in these cyst fluid samples. Ingenuity Pathway Analysis (IPA) analysis indicated that the genes targeted by the differentially enriched cyst fluid miRNAs are involved in five canonical signaling pathways, including molecular mechanisms of cancer and signaling pathways implicated in colorectal, ovarian and prostate cancers. Our findings make a compelling case for undertaking in-depth analyses of cyst fluid miRNomes for developing informative early detection biomarkers of pancreatic cancer developing from pancreatic cystic lesions.